METASTATIC CARDIAC CANCER - A CASE REPORT: Metastatic Cardiac Cancer - Zaidi, Syed Shahid Nafees; Ali, Nasir; Bakht, Nausheen; Iqbal, Tahir; Atique, Muhammad (Pakistan Armed Forces Medical Journal, 2015)
Introduction CASE REPORTSFigure-1: Operative field showing tumor tissue.Cardiac cancer is an extremely rare entity in medical literature. In one review paper, out of 12,000 autopsies only 7 were cancers of primary cardiac origin. Whereas metastatic cardiac cancer is relatively less rare and out of 3000 autopsies 15 were metastatic cardiac cancer1. Patients’ signs and symptoms depend upon the involvement of right and/ or left heart system. Sarcomas constitute the majority of malignant cardiac tumors whereas Myxomas are the common benign tumors2.  Metastatic cardiac cancer can find their way from primaries of lung, liver, breast and prostate, to name a few. Primary or secondary  malignant cardiac tumors pose significant  technical problems due to widespread involvement and specially in  secondary metastatic cardiac cancer, one cannot always locate the primary cancer site despite detailed and careful work-up, hence the survival rate is thus quite low3. This case report pertains to a metastatic cardiac malignancy in which we could not find the primary cancer site pre-operatively.